2015
DOI: 10.1002/2015gl066908
|View full text |Cite
|
Sign up to set email alerts
|

Annual variation and synodic modulation of the sporadic meteoroid flux to the Moon

Abstract: The Lunar Dust Experiment on board NASA's Lunar Atmosphere and Dust Environment Explorer discovered a permanently present, asymmetric dust cloud engulfing the Moon, sustained by meteoroid bombardment. It is most dense at 5–8 lunar local time, with a peak density canted sunward. Here we present analysis on the variation of the cloud density during January to April 2014. We find the lunar dust cloud in the Moon's equatorial plane to be dominantly produced by impacts from three known sporadic meteoroid sources: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 20 publications
2
63
0
Order By: Relevance
“…We conclude in this work that the meteoroid environment is not the main source of the H/AH imbalance in the LDEX observations reported by Szalay and Horányi (2015). In our model the H and AH sources are approximately equal in terms of the total mass influx on the lunar surface, with small variations during the year due to the Moon's motion.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…We conclude in this work that the meteoroid environment is not the main source of the H/AH imbalance in the LDEX observations reported by Szalay and Horányi (2015). In our model the H and AH sources are approximately equal in terms of the total mass influx on the lunar surface, with small variations during the year due to the Moon's motion.…”
Section: Discussionmentioning
confidence: 49%
“…Initial results reported by Szalay and Horányi (2015) (hereafter referred as SH15) found that the ejecta cloud in the Moon's equatorial plane is primarily produced by impacts from a combination of the three known sporadic meteoroid sources (Helion, Anti-Helion, and Apex). Initial results reported by Szalay and Horányi (2015) (hereafter referred as SH15) found that the ejecta cloud in the Moon's equatorial plane is primarily produced by impacts from a combination of the three known sporadic meteoroid sources (Helion, Anti-Helion, and Apex).…”
Section: 1002/2017gl076065mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we expand that fit to include the high‐latitude NT/ST sources (Pokorný et al, ). Each source is modeled as a collimated beam from a specific radiant direction, and the subsequent impact ejecta response is assumed to follow M+Fmmαvβcos2φ, where m is the characteristic mass of the impactors, F m is the mass flux, v is the impactor speed, α = 0.23 and β = 2.46 are experimentally determined constants, and φ is the angle of impact ejecta relative to the surface normal (Gault et al, ; Koschny & Grün, ; Szalay & Horányi, ). Equation is given as a proportionality relation since M + is scaled to the actual lunar values derived by LDEX measurements, described below.…”
Section: Ejecta Model Descriptionmentioning
confidence: 99%
“…The production of detectable of amounts material by impacts has been verified around the Moon in LADEE neutral mass spectra where periodic spikes in the exosphere density correlate with known orbital crossing meteorite streams [Szalay and Horányi, 2015]. While dust impacts may generate detectable amounts of ejecta, they are neglected in this analysis since the calculations have already been carried elsewhere out for the martian moons [Cipriani et al, 2011].…”
Section: Exosphere Production Around Small Bodiesmentioning
confidence: 92%